쑥을 첨가한 곤약국수의 제조 및 특성 - 김석지(Seog-Ji Kim) (東아시아食生活學會誌, 2013)
Konjac gel is known as a low calorie food, because the main component is water. Mugwort has been used for food and medicine for a long time due to itsfunctional property, which contains a lot of vitamins and minerals. Therefore, konjac noodle-added mugwort was prepared. The konjac gel was made by from a centrifuge after adding water, alkali and mugwort power in konjac flour. The centrifuge was used to remove air in the gel. After centrifuging by heating the gel in boiling water for one hour, konjac noodle was made by pressing using a flat heating press. The results are as follows. In the drying process of mugwort freeze drying after blanching in 1% $NaHCO_3$ solution is better than other drying methods. The physical properties (hardness, elasticity, cohesiveness, gumminess) of konjac gel were measured with a Rheometer. The optimum processing conditions were decided by these measured values. The optimum condition of making konjac gel is 9% concentration of konjac flour, a ph of 12.0, $Na_3PO_4$ coagulant and 1.5% concentration of mugwort power in konjac flour. 본 연구는 저칼로리 식품으로 알려져 있는 곤약과 약리작용이 뛰어난 쑥을 첨가한 곤약국수를 제조하고자 쑥의 건조방법에 따른 색도 변화와 곤약분말 농도, pH, 응고제의 종류에 따른 곤약 겔의 제조조건과 쑥의 첨가량에 따른 최적의 곤약국수의 제조방법을 조사하였다. 곤약국수에 사용할 쑥의 건조방법별 색도 변화 조사 결과, 1% $NaHCO_3$ 용액에 데친 후 건조한 방법(HADB, FDB)은 데치지 않은 방법(HAD, FD)에 비하여 쑥의 녹색유지에 효과적이었고 데친 후 동결건조한 방법(FDB)은 데친 후 열풍건조한 방법(HADB)에 비하여 선명한 녹색을 띄고 있었다. 따라서 쑥 가공처리에 있어서 1% $NaHCO_3$ 알칼리 용액에 데친 후, 동결건조방법이 쑥의 녹색을 유지하는데 가장 효과적이었다. 곤약 겔의 최적의 제조조건을 조사하고자 곤약분말의 농도, pH, 응고제의 종류에 따른 곤약 겔의 물성(견고성, 탄력성, 응집성, 점착성)을 측정하였으며, 그 결과, 분말농도는 9%, pH는 12, 응고제는 $Na_3PO_4$를 사용했을 때 물성치가 우수하게 나타났다. 쑥의 첨가량의 영향을 분석한 결과, 곤약분말에 대하여 1.5% 첨가가 색, 향, 맛 등 전반적인 기호도가 높게 나타나, 1.5% 첨가하는 것이 바람직할 것으로 판단되었다. 이상의 결과로부터 제시한 곤약의 제조 방법과 적절한 농도의 쑥을 첨가한 곤약국수를 제조하여 영양적, 물성적, 관능적으로 소비자들에게 긍정적인 반응을 보일 수 있는 제품이 제조될 수 있는 기초자료로 활용될 수 있다고 사료된다.